Ultrastructural Mechanisms of Deformation and Failure in Wood Under Tension - Saavedra-Flores, E (2013)
This paper investigates the deformation and failure mechanisms of wood at the ultrastructural scale. At this level, wood is composed of a periodic alternation of amorphous and crystalline cellulose fractions, embedded in a soft hemicellulose-lignin matrix. The mechanical response of wood is calculated under tensile loading conditions by means of the computational homogenisation of a representative volume element (RVE) of material. Three potential mechanisms of failure are suggested: axial straining of the crystalline fraction of cellulose, accumulation of plastic strain in the amorphous portion of cellulose and tensile rupture in the hemicellulose-lignin matrix due to cellulose fibres separation. In order to validate the present multi-scale framework, we compare our numerical predictions for the reorientation of cellulose fibres with experimental data, finding a good agreement for a wide range of strains. Furthermore, we assess successfully our numerical predictions for ultimate strains at the instant of failure when compared to experimental values. Numerical simulations show that our model is able to provide new clues into the understanding of how trees and plants optimise their microstructure in order to develop larger strains without apparent damage. A remarkable prediction by our model suggests that the extensibility of the material is maximised for initial microfibril angles (MFA) between 50 and 55, a range of values found typically in branches of trees, in which the extensibility is an essential requirement. These findings are likely to shed more light into the dissipative mechanisms of wood and natural materials, which are still not well-understood at present. © 2013 Elsevier Ltd. All rights reserved.